Odpowiedzi

2010-01-26T15:57:00+01:00
A)
8x-6y=10
7x+y=5/*6

8x-6y=10
42x+6y=30

50x=40/:50
x=0,8

x=0,8
8*0,8-6y=10

x=0,8
6,4-6y=10

x=0,8
-6y=10-6,4

x=0,8
-6y=3,6/:(-6)

x=0,8
y=-0,6

b)
4(x-2)-(y-2)=1
10x-2y=18

4x-8-y+2=1
10x-2y=18

4x-y=1+8
10x-2y=18

4x-y=9/*(-2)
10x-2y=18

-8x+2y=-18
10x-2y=18

2x=0/:2
x=0

x=0
4*0-y=9

x=0
0-y=9

x=0
-y=9/:(-1)

x=0
y=-9

c)
12q-7r=-16/*(-3)
q-3r=-69/*7

-36q+21r=48
7q-21r=-483

-29q=-435
q=15

q=15
12*15-7r=-16

q=15
180-7r=-16

q=15
-7r=-16-180

q=15
-7r=-196/:(-7)

q=15
r=28

e)
x+4y=1/*2
x-8y=-1

2x+8y=2
x-8y=-1

3x=1/:3
x=⅓

x=⅓
⅓+4y=1

x=⅓
4y=1-⅓

x=⅓
4y=⅔/:4

x=⅓
y=⅙

nie zrobiłam wszystkich, bo nie wszystkie umiałam, przykro mi ;/
mam nadzieję,że chociaż to ci się przyda ;]





















Najlepsza Odpowiedź!
2010-01-26T16:01:24+01:00
A)
8x-6y=10
7x+y=5|*6

8x-6y=10
42x+6y=30
50x=40
x=0,8

6,4-6y=10
-6y=3,6
y=-0,6

b)
4(x-2)-(y-2)=1
10x-2y=18

4x-8-y+2=1
10x-2y=18

4x-y=7|*(-2)
10x-2y=18

-8x+2y=-14
10x-2y=18
2x=4
x=2

8-y=7
-y=-1
y=1

c)
12p-7n=-16|*(-3)
p-3r=-69|*7

-36p+21n=48
7p-21n=-483
-29p=-435
p=15

180-7n=-16
-7n=-196
n=28

d)
x-4y=15|*4
y=4x

4x-16y=60
y=4x
-15y=60
y=-4

x+16=15
x=-1


e)
x+4y=1|*2
x-8y=-1

2x+8y=2
x-8y=-1
3x=1
x=1/3

1/3+4y=1
4y=2/3
y=1/6


f)
5e-2f=8
-5e+f=-f
2f=8
f=4

5e-8=8
5e=16
e=3,2